2014
DOI: 10.1038/ncomms6761
|View full text |Cite
|
Sign up to set email alerts
|

Intra-unit-cell nematic charge order in the titanium-oxypnictide family of superconductors

Abstract: Understanding the role played by broken-symmetry states such as charge, spin and orbital orders in the mechanism of emergent properties, such as high-temperature superconductivity, is a major current topic in materials research. That the order may be within one unit cell, such as nematic, was only recently considered theoretically, but its observation in the iron-pnictide and doped cuprate superconductors places it at the forefront of current research. Here, we show that the recently discovered BaTi 2 Sb 2 O s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(68 citation statements)
references
References 49 publications
(92 reference statements)
13
55
0
Order By: Relevance
“…There are three possible sources for considerable V : (i) Strongly correlated metals are generally bad metals with large resistivity of the order of mΩ·cm and small optical Drude peak. Therefore, the electrostatic screening does not work well in those systems [14,[75][76][77][78]. (ii) In mean-field theory, the local constraint of no-double occupancy at each site is reinforced only globally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are three possible sources for considerable V : (i) Strongly correlated metals are generally bad metals with large resistivity of the order of mΩ·cm and small optical Drude peak. Therefore, the electrostatic screening does not work well in those systems [14,[75][76][77][78]. (ii) In mean-field theory, the local constraint of no-double occupancy at each site is reinforced only globally.…”
Section: Discussionmentioning
confidence: 99%
“…This generally yields a dome structure of the SC critical temperature T c as a function of the doping level x. The parent competing order (CO) ranges from the antiferormagnetic spin order in cuprates [4][5][6][7][8] and heavy-fermion rare-earth compounds [9], to the ferro-orbital and antiferormagnetic spin dipolar/quadruplar orders in iron pnictides/chalcogenides [10][11][12][13], and to the charge order in titanium oxypnictides [14] and transition-metal dichalcogendies [15]. A particularly interesting case is the cuprate high-temperature superconductors, where the parent and SC phases do not appear to coexist but the phase competition is actually intensified by the emerging of a "strange metal" normal state with pseudogap opening at a temperature T * well above T c in the underdoped regime [5].…”
Section: Introductionmentioning
confidence: 99%
“…The increased relaxation of the polarization could not be found below TDW, indicating the absence of magnetic order. Frandsen et al performed low-temperature neutron diffraction measurements and found tiny lattice distortions from tetragonal to orthorhombic where the orthorhombicity parameter η = 2 × (a − b)/(a + b) reaches only 0.22% and 0.05% at 20 K for BaTi2As2O and BaTi2Sb2O, respectively [19]. The lattice distortion is much smaller than that observed in Jahn-Teller compounds and iron pnictides.…”
Section: The Dw Instability In Bati 2 Pn 2 Omentioning
confidence: 99%
“…At present, eight titanium pnictide oxides Na 2 Ti 2 Pn 2 O (Pn = As, Sb), (SrF) 2 Ti 2 Pn 2 O (Pn = As, Sb, Bi), and BaTi 2 Pn 2 O (Pn = As, Sb, Bi) have been synthesized, but only BaTi 2 Pn 2 O (Pn = Sb, Bi) shows superconductivity [11,[14][15][16][17]. Though BaTi 2 Pn 2 O is not high-T c superconductor, several unique and attracting physical properties have been found: two superconducting domes in the phase diagram of isovalent solid solutions of BaTi 2 (Sb 1-x Bi x ) 2 O and unconventional DW instability [18,19]. In this short review, the superconductivity and DW instability in the titanium pnictide oxides will be discussed from discovery to recent progress.…”
Section: Introductionmentioning
confidence: 99%
“…The double stripe (DS) magnetic ground state has been proposed in BaTi 2 Sb 2 O [20][21][22][23] and found in the 11 system Fe 1+y Se x Te 1−x [24,25], which exhibits magnetic order with the commensurate ordering vector Q = (π/2,π/2) [26][27][28]. DS order can be understood as the Néel ordering of a four-spin plaquette with three up and one down spins, which results in double-width ferromagnetic (FM) stripes along one diagonal direction and double-width antiferromagnetic(AFM) stripes along the other, see Fig.…”
Section: Introductionmentioning
confidence: 99%